Sistema de monitoramento de máquinas elétricas via TCP/IP - Magril Júnior, Luís Carlos (2015)
In this work it is developed a monitoring system of electrical quantities of electrical machines, which can provide the data via TCP/IP protocol. The data of interest are the waveforms of current and voltage that feed the machines. To accomplish the acquisition of these data, sensing and conditioning boards were developed, in conjunction with an analog-to-digital conversion system that sample and sends the data to the user that is requesting in the network. The elaboration of the necessary systems were made in a way that it have the lowest cost possible. It developed a control and visualization interface of the data in the software Matlab, where the user can select the sample frequency and the operation modes available for the acquisition of the data. The operation modes that are available to the user are the acquisition in steady state, acquisition in transient state and automatic update. The system developed can be used in various forms as means of acquisition of the electrical signals for further studies. However, it can also be applied in the learning of electrical machines, where the student can observe the electrical behavior of the machines simply by using the system.